Strategi Segmenting dan Targeting pada KISI Sekuritas Cabang Sumatra Barat - Aisyatur Rahmi; Gilang Rahamdhan; Ahmad Vajri Rahman (CV. ITTC INDONESIA, 2026)
The development of the capital market industry in Indonesia requires securities companies to have appropriate marketing strategies to effectively reach potential investors. One important strategy in marketing is segmentation and targeting. This paper aims to analyze the segmentation and market targeting strategies implemented by KISI Securities, West Sumatra Branch, to attract and retain investors. The writing method used is a qualitative descriptive study by reviewing data and information sourced from literature, company documents, and observations of KISI Securities' marketing activities, Padang Branch. The results of the discussion indicate that KISI Sekuritas implemented a segmented marketing strategy by dividing the market into several main segments, namely the student and pupil segment, professionals and young workers, and the active investor community. Segmentation was carried out based on geographic, demographic, psychographic, and behavioral aspects. The primary target market of KISI Sekuritas Padang Branch is students and the younger generation because they have long-term potential, while the secondary market target is professionals with a fixed income. Educational strategies, the use of digital media, and collaboration with educational institutions are the main approaches in implementing targeting. With this strategy, KISI Sekuritas is able to increase investment literacy and expand the investor base in the West Sumatra region.